Ответ(ы) на вопрос:
Гость
3) [latex] \frac{1}{x-2} +\frac{x}{x+2}=\frac{4}{x^2-4}-\frac{2x}{x+2} [/latex]
x≠2 и x≠-2
[latex] \frac{(x+2) +x(x-2)}{(x+2)(x-2)}=\frac{4-2x(x-2)}{(x+2)(x-2)}[/latex]
(x+2) +x(x-2)=4-2x(x-2)
x+2 +x²-2x=4-2x²+4x
x²-x+2=4-2x²+4x
3x²-5x-2=0
D=5²+4*3*2=25+24=49
√D=7
x₁=(5-7)/6=-1/3
x₂=(5+7)/6=2 при x=2 знаменатели (х-2) и (х²-4) обращаются в 0 - отбрасываем
Ответ: -1/3
4) [latex] \frac{6}{x^2-9} + \frac{3x}{x-3} = \frac{1}{x+3}+ \frac{5x}{x-3} [/latex]
x≠3 и x≠-3
[latex] \frac{6+3x(x+3)}{(x+3)(x-3)} = \frac{(x-3)+5x(x+3)}{(x+3)(x-3)}[/latex]
6+3x(x+3) = (x-3)+5x(x+3)
6+3x²+9=x-3+5x²+15x
2x+7x-9=0
D=7²+4*2*9=49+72=121
√D=11
x₁=(-7-11)/4=-18/4=-9/1=-4,5
x₂=(-7+11)/4=1
Ответ: х=-4,5 и х=1
Не нашли ответ?
Похожие вопросы